Currículo como direito de aprendizagem: uma experiência nacional para o ciclo de alfabetização - Couto, Lucia Helena (2014)
This research is based on the fact that the national curriculum is still not defined and implemented, despite the fact that it was mentioned in the Federal Constitution (BRASIL, 1988) and the Law of Guidelines and Bases of National Education (BRASIL, 1996). This fact implicates on vulnerability in the national educational system, specifically in the teaching process. The National Curriculum Guidelines for K-9 Education in Nine Years (BRASIL, 2010) established, in article 49, that the Ministry of Education would define the learning expectations for each year of elementary and middle school, in a process involving public debate. The objective of this research is to analyze this assignment, its strategies and the concepts produced. The focus is the document developed in 2012 by the Ministry of Education and delivered to the National Council of Education entitled Elementos conceituais e metodológicos para definição dos direitos de aprendizagem e desenvolvimento do ciclo de alfabetização (1º, 2º e 3º ano) do ensino fundamental . In the analysis process, we used activities reports and information concerning the various actors that were involved in the process of the elaboration of the document above mentioned. The participatory methodology and the involvement of public educational systems in the evaluation and organization of the document content were essential elements in the research. The analysis and the evaluation of the reports revealed that the task to define the learning rights in each school year was a result of a participatory process that was consensual among specialists from various universities, school managers and teachers. This research concluded that, despite the fact the document was not carried on by the National Council of Education, it represented the first and successful experience in defining the learning needs in each of the school years and in expressing the right to learn guaranteed by the law